2022
DOI: 10.3390/electronics11091366
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Management Issues and Solutions in 5G-and-Beyond Networks: A Comprehensive Review

Abstract: The fully accomplished standardization of the new mobile generation has led to the deployment of fifth-generation (5G) wireless networks to gratify enormous traffic volume for Internet services. The current centralized mobility system could not be sufficient to manage an explosive increase in data volume and is considered a steadily rising issue in modern wireless communication. A new technique that can affluently handle traffic problems and completely avoid network breakdown chances is indispensable. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 136 publications
0
10
0
1
Order By: Relevance
“…One of such requirements is backhaul link management, which occurs due to composing a large number of small cells based dense radio access network. SDN has emerged as a promising approach for handling the Distributed Mobility Management (DMM) paradigm in dense wireless communication [85]. The authors in [86] suggested an SDN-based implementation for IPv6 compatible MAC layer control through Southbound API (Application Layer Interface) in SDN.…”
Section: A Distributed Mobility Managementmentioning
confidence: 99%
“…One of such requirements is backhaul link management, which occurs due to composing a large number of small cells based dense radio access network. SDN has emerged as a promising approach for handling the Distributed Mobility Management (DMM) paradigm in dense wireless communication [85]. The authors in [86] suggested an SDN-based implementation for IPv6 compatible MAC layer control through Southbound API (Application Layer Interface) in SDN.…”
Section: A Distributed Mobility Managementmentioning
confidence: 99%
“…On the other hand, in order to effectively deploy D2D communication technology, a number of problems must be resolved. D2D technology needs efficient power and spectrum allocation algorithms, advanced interference mitigation methods, and intelligent mode selection and mobility strategies [67]. Many research investigations in D2D communications have been introduced to realize different aspects of D2D technology.…”
Section: Related Work and Contributionmentioning
confidence: 99%
“…A new solution for managing mobility should be created to provide seamless changeover for 5G new radio in network slicing. The management of mobility is divided into two levels of mode: idle mode for user reachability and connected mode for handover, making mobility one of the major concerns in a service level for future networks [18]. According to the explanation of the mobility management architecture in [19] based on network slicing, each slice maintains its users across various radio access technologies.…”
Section: Literature Reviewmentioning
confidence: 99%